2010
DOI: 10.1007/s00535-010-0312-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of RAPID® 5 Access software for examination of capsule endoscopies and reading of the capsule by an endoscopy nurse

Abstract: RAPID(®) 5 Access improves diagnostic yield, reducing reading time; however, it is still unacceptable because of the diagnostic miss rate and may be useful as an ancillary reading tool. Developing further improved software and training expert assistants for reading capsule images are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 12 publications
1
23
0
1
Order By: Relevance
“…In previous trials, the mean reading time of the nurses was slightly longer than that of the physicians [15,16]. However, the trained endoscopy nurse detected 93-94% of the clinically significant lesions seen by the physician [12,16].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In previous trials, the mean reading time of the nurses was slightly longer than that of the physicians [15,16]. However, the trained endoscopy nurse detected 93-94% of the clinically significant lesions seen by the physician [12,16].…”
Section: Discussionmentioning
confidence: 85%
“…The quickview mode generates a preview of the entire CE recording selecting the "images of interest" according to the analysis of colors and image patterns. But its diagnostic miss rate was described as 8% and 10% [14,15] in two studies; thus, the quickview mode cannot substitute for a complete reading of the CE video.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The addition of applications such as the (Lewis score, Rapid atlas, colon localization track, circumstance scale) also improved the efficiency of reading and reporting. This version enhance workflow can forward multiple exams simultaneously and RAPID 5 Access software has been shown to improve diagnostic yield while reducing reading time (Shiotani et al, 2011). RAPID 6 supports the PillCam Sensor Belt, a "patient-friendly" alternative to the sensorArray and its stick-on adhesive sleeves.…”
Section: Video Capsule Reading Softwarementioning
confidence: 99%
“…This study used much higher video speeds (up to 36 frames per second; fps) resulting in a fairly rapid conventional viewing time of approximately 17 min. When the Quickview system was used in a study in Japan 10% missed diagnoses were reported [11]. The average reading time for 14 volunteers with aspirin-induced injury was 32.6 min in conventional mode (at 12 fps) and 17.9 min in Quickview mode (at 6 fps).…”
Section: Introductionmentioning
confidence: 98%